Plant disease diagnostic capabilities and networks - Miller, S.A.; Beed, Fenton D.; Harmon, C.L. (Annual Reviews, 2009)
Emerging, re-emerging and endemic plant pathogens continue to chal-lege our ability to safeguard plant health worldwide. Further, global-ization, climate change, increased human mobility, and pathogen andvector evolution have combined to increase the spread of invasive plantpathogens. Early and accurate diagnoses and pathogen surveillance onlocal, regional, and global scales are necessary to predict outbreaks andallow time for development and application of mitigation strategies.Plant disease diagnostic networks have developed worldwide to addressthe problems of efficient and effective disease diagnosis and pathogendetection, engendering cooperation of institutions and experts withincountries and across national borders. Networking maximizes impact inthe face of shrinking government investments in agriculture and dimin-ishing human resource capacity in diagnostics and applied pathology.New technologies promise to improve the speed and accuracy of diseasediagnostics and pathogen detection. Widespread adoption of standardoperating procedures and diagnostic laboratory accreditation serve tobuild trust and confidence among institutions. Case studies of national,regional, and international diagnostic networks are presented.